La vulneración del derecho a la defensa en la falta de técnicas de argumentación y litigación oral en la audiencia de juicio en el procedimiento ordinario de conformidad con el Código Orgánico Integral Penal. - Donoso Calderón, Ernesto Alonso (2025)
In compliance with the principle of orality, the procedures of the Ecuadorian judicial system are conducted through hearings, which, in addition to guaranteeing the principle of immediacy, provide attorneys with the opportunity to present their arguments orally and in direct contact with the judge. This interaction is essential within the process, as it allows for the presentation of the theory of the case, the examination of evidence, and all necessary elements to persuade the judge that their claims are substantiated and that a favorable ruling should be issued in their client's interest. The final stage of the criminal process is adjudicated by three judges and is no longer based on elements of conviction but rather on evidence. In other words, the tribunal is tasked with resolving the legal status of one or more individuals concerning deprivation of liberty. In this context, during the trial hearing, it is crucial for the litigating attorney, in the technical defense of either party, to be well-prepared in oral argumentation and litigation techniques. This preparation involves the proper use of language, the selection of a flexible and adaptable narrative discourse, and improving communication skills. Furthermore, Article 76, numeral 7 of the Constitution of the Republic of Ecuador enshrines the right to a defense, enumerating several constitutional guarantees, including the possibility of presenting arguments or reasons verbally, seeking assistance, refuting the arguments of other parties, presenting evidence, and contesting the evidence presented against them. The lack of optimal oral advocacy techniques by attorneys may result in a violation of the right to defense. To address this issue, various existing techniques of oral argumentation and litigation were compiled from legal doctrine and research. The role of attorneys in oral advocacy during trial hearings was analyzed, along with the components and scope of the right to defense. This analysis was complemented by data collected from attorneys with experience in criminal litigation, confirming the constitutional violations stemming from deficient oral advocacy. The methodology employed was mixed, incorporating both quantitative and qualitative approaches. It was concluded that the attorney's role and stance during the hearing are critical in selecting the appropriate oral argumentation and litigation technique to ensure an effective technical defense and safeguard the client’s right to defense.